2008
DOI: 10.1088/0022-3727/41/12/125406
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties and phase transitions in perovskite Pb[Zr1−x(Ni1/3Nb2/3)x]O3(0.0 ⩽x⩽ 0.5) ceramics

Abstract: A solid solution of lead zirconate–lead nickel niobate ceramics, Pb[Zr1−x(Ni1/3Nb2/3)x]O3 (PZNN) with x = 0.0–0.5, was synthesized via the columbite precursor method. The crystal structures as well as the thermal and dielectric properties were investigated in terms of the lead nickel niobate (PNN) concentration. X-ray diffraction indicated that all samples exhibited a single-phase perovskite structure. At room temperature, Pb[Zr1−x(Ni1/3Nb2/3)x]O3 is orthorhombic for a composition where x = 0, rhombohedral for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…Choi et al [22] reported that in the Bi(Ni 1/2 Ti 1/2 )O 3 -PbTiO 3 (BNiT-PT), the tricritical point in the solid solution also corresponded closely to t ∼ 1.0. Similar phenomena have been observed in the Bi(Mg 3/4 W 1/4 )O 3 -PbTiO 3 (BMW-PT) system by Stringer et al [23] and our previous work on PbZrO 3 related materials [24,25].…”
Section: Resultssupporting
confidence: 87%
“…Choi et al [22] reported that in the Bi(Ni 1/2 Ti 1/2 )O 3 -PbTiO 3 (BNiT-PT), the tricritical point in the solid solution also corresponded closely to t ∼ 1.0. Similar phenomena have been observed in the Bi(Mg 3/4 W 1/4 )O 3 -PbTiO 3 (BMW-PT) system by Stringer et al [23] and our previous work on PbZrO 3 related materials [24,25].…”
Section: Resultssupporting
confidence: 87%
“…[8,10] or (Pb,Ba)ZrO 3 [5,7]. Nevertheless, at high temperature, the dielectric data revealed an enhanced dielectric loss with increasing BAO concentration.…”
Section: Dielectric Propertiesmentioning
confidence: 92%
“…The FE intermediate phase can be induced by adding Ba 2+ , Sr 2+ , and La 3+ at the Pb 2+ -site [2,[4][5][6][7]. Moreover, our recent research found that the FE intermediate phase also can be induced by adding, for example, hybrid-doped Ni 2+ /Nb 5+ , Zn 2+ /Nb 5+ , Co 2+ /Nb 5+ and Mg 2+ /W 6+ at the Zr 4+ -site [8][9][10][11][12][13][14]. BiMO 3 ; M = Fe 3+ , Mn 3+ and Nd 3+ has received a lot of attention recently as a multiferroic, and investigation of the solid solutions, BiMO 3 -PbTiO 3, has shown that they improve ferroelectric properties of PbTiO 3 , reduce the amount of lead, and find new morphotropic phase boundary piezoelectrics [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our research work reported that the intermediate phase can also be introduced by partial replacement of Zr 4+ ions with complex B-site ions such as Ni 2+ /Nb 5+ [23,24], Zn 2+ /Nb 5+ [25], or Co 2+ /Nb 5+ [26]. Furthermore, our previous study found that by adding minor amounts (2-10 mol%) of antiferroelectric Pb(Mg 1/2 W 1/2 )O 3 (PMW) into antiferroelectric PZ, the temperature range expanded to an intermediate phase, which was characterized by evident frequency dispersion in dielectric permittivity [27].…”
Section: Introductionmentioning
confidence: 99%